The eucharist in St John's Gospel : an examination of the extent to which it is justifiable to see allusions to the eucharist in St John's Gospel - Verryn, Paul (Rhodes University, Faculty of Divinity, Department of Divinity, 1979)
This thesis shows that the incarnation of Jesus Christ is an ever present reality for St. John. Christ's abiding presence is known to those who are committed to him because he is their Saviour and Lord. This presence is especially real when his disciples, the believers, the Church gather for worship. In the eucharist, which is an act of worship, the meaning and purpose of the incarnation becomes apparent for St. Paul. By showing that aspects of John's understanding of the incarnation co-incide with the early Church's doctrine of eucharist (as portrayed by St. Paul) the conclusion is reached that we have eucharistic allusions in the gospel of John. Furthermore, John presents Jesus in contrast to the Old Covenant. Jesus supersedes the Old Covenant and establishes the new covenant of love. Just as the Old Covenant was celebrated in the Passover, so the eucharist re-enacts the new covenant. By alluding to the old sacrament, John shows how the eucharist fulfils the true meaning of Passover. After a brief examination of existing methodologies, I present the working hypothesis for this dissertation as outlined above. In a fairly detailed exegesis of Jn 6 (with digressions to other relevant passages in John) which is divided into three sections (In 6:1-21 6:22-48, 6:49-71), I have tried to show that John sees the eucharist as a celebration which emphasises the community of the church, which re-enacts God's great demonstration of love (typified especially in the death of Jesus) and which foreshadows that great heavenly banquet, when, all will be gathered to him. I reach the conclusion therefore that we are justified in finding allusions in the eucharist in the gospel of John.
Keywords: Bible -- John -- Commentaries; Lord's Supper